Noninvasive Ventilation and Mechanical Insufflator-Exsufflator for Acute Respiratory Failure in Children With Neuromuscular Disorders - Chen, Tai-Heng; Hsu, Jong-Hau (Frontiers in Pediatrics, 2020)
Children with neuromuscular disorder (NMD) usually have pulmonary involvement characterized by weakened respiratory muscles, insufficient coughing, and inability to clear airway secretions. When suffering from community-acquired pneumonia, these patients are more likely to develop acute respiratory failure (ARF). Therefore, recurrent pneumonias leading to acute on chronic respiratory failure accounts for a common cause of mortality in children with NMD. For many years, noninvasive ventilation (NIV) has been regarded as a life-prolonging tool and has been used as the preferred intervention for treating chronic hypoventilation in patients with advanced NMD. However, an increasing number of studies have proposed the utility of NIV as first-line management for acute on chronic respiratory failure in NMD patients. The benefits of NIV support in acute settings include avoiding invasive mechanical ventilation, shorter intensive care unit or hospital stays, facilitation of extubation, and improved overall survival. As the difficulty in clearing respiratory secretions is considered a significant risk factor attributing to NIV failure, combined coughing assistance of mechanical insufflator-exsufflator (MI-E) with NIV has been recommended the treatment of acute neuromuscular respiratory failure. Several recent studies have demonstrated the feasibility and effectiveness of combined NIV and MI-E in treating ARF of children with NMD in acute care settings. However, to date, only one randomized controlled study has investigated the efficacy of NIV in childhood ARF, but subjects with underlying NMD were excluded. It reflects the need for more studies to elaborate evidence-based practice, especially the combined NIV and MI-E use in children with acute neuromuscular respiratory failure. In this article, we will review the feasibility, effectiveness, predictors of outcome, and perspectives of novel applications of combined NIV and MI-E in the treatment of ARF in NMD children.